1996
DOI: 10.1007/bf01799106
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of pyruvate carboxylase and the pyruvate dehydrogenase complex

Abstract: The most common defect associated with deficiency of the pyruvate dehydrogenase (PDH) complex occurs in the E1 component, specifically due to mutations in the X-linked E1 alpha gene. Clinical sequelae of these mutations, which range from severe neonatal lactic acidosis to carbohydrate-sensitive ataxia, can be different in males and females depending on the nature of the mutation and, in the case of females, on the X-inactivation pattern in different tissues. Males have a high representation of missense mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
163
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(176 citation statements)
references
References 31 publications
10
163
0
3
Order By: Relevance
“…The fixed difference gives rise to a synonymous polymorphism (GCA and GCG codons for alanine) and so is probably not under selection. PDHA1 is a subunit of the pyruvate dehydrogenase enzyme, and a number of mutations have been described that disrupt gene function and cause disease (37), but no reports have been found that inform on whether, or to what extent, there exist geographically restricted functional variants.…”
Section: Resultsmentioning
confidence: 99%
“…The fixed difference gives rise to a synonymous polymorphism (GCA and GCG codons for alanine) and so is probably not under selection. PDHA1 is a subunit of the pyruvate dehydrogenase enzyme, and a number of mutations have been described that disrupt gene function and cause disease (37), but no reports have been found that inform on whether, or to what extent, there exist geographically restricted functional variants.…”
Section: Resultsmentioning
confidence: 99%
“…It consists of multiple copies of three different enzymes: the thiamine-dependent pyruvate decarboxylase (E1) is a heterotetrameric (α 2 β 2 ) protein that irreversibly oxidizes pyruvate to acetyl CoA; dihydrolipoamide acetyl-transferase (E2) forms the structural core of the complex; dihydrolipoamide dehydrogenase (E3) is stably integrated into the complex by an E3-binding protein (E3bp), formally called protein X, that has no known enzymatic function [1]. Rapid regulation of the complex in eukaryotes occurs primarily by reversible phosphorylation of serine residues in the E1α subunit by PDH kinase and PDH phosphatase, in which the unphosphorylated enzyme is catalytically active [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Its clinical presentation and course are variable but most patients exhibit progressive neurological degeneration and either persistent or episodic elevation of lactate in blood, cerebrospinal fluid or both [2][3][4]. By far the majority of biochemically proven cases of PDH deficiency are due to defects in the E1α subunit.…”
Section: Introductionmentioning
confidence: 99%
“…Dysmorphism and brain malformations are found in some patients including microcephaly, narrow head, wide nasal bridge, and agenesis of corpus callosum (75,76). In some patients, there is generalised hypomyelination, and others have small cystic lesions and gliosis in the cortex, basal ganglia, brain stem, or cerebellum.…”
Section: Energy Deficiency Typementioning
confidence: 99%